Feedback type as a moderator of the relationship between achievement goals and feedback reactions. - Anseel, Frederik; Van Yperen, Nico W.; Janssen, Onne; Duyck, Wouter (Journal of Occupational & Organizational Psychology, 2011)
The aim of the current study is to shed new light on the inconsistent relationship between performance-approach (PAp) goals and feedback reactions by examining feedback type as a moderator. Results of a field experiment ( N = 939) using a web-based work simulation task showed that the effect of achievement-approach goals was moderated by feedback type. Relative to individuals pursuing mastery-approach goals, individuals pursuing PAp goals responded more negatively to comparative feedback but not to task-referenced feedback. In line with the hypothesized mediated moderation model, the interaction between achievement goals and feedback type also indirectly affected task performance through feedback reactions. Providing employees with feedback is a key psychological principle used in a wide range of human resource and performance management instruments (e.g., developmental assessment centres, multi-source/360° feedback, training, selection, performance appraisal, management education, computer-adaptive testing, and coaching). The current study suggests that organizations need to strike a balance between encouraging learning and encouraging performance, as too much emphasis on comparative performance (both in goal inducement and in feedback style) may be detrimental to employees' reactions and rate of performance improvement.